2017
DOI: 10.1002/jmri.25755
|View full text |Cite
|
Sign up to set email alerts
|

Isotropic three‐dimensional T2 mapping of knee cartilage: Development and validation

Abstract: 1 Technical Efficacy: Stage 2 J. Magn. Reson. Imaging 2018;47:362-371.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 44 publications
1
12
0
Order By: Relevance
“…T 2 maps generated from 2D TSE by traditional exponential fitting, which is the most common acquisition pipeline in clinical studies, show poor T 2 accuracy. 32,33 New fitting methods, such as noisecorrected 33 and library-based fitting approaches, 34 along with new 3D acquisition schemes (quantitative double-echo steady-state 35,36 or isotropic 3D T 2 -prepared gradientecho 37 ), which enables higher in-plane spatial resolution and smaller slice thickness, may facilitate reproducible and precise T 2 estimates without the partial volume effect etc.…”
Section: Discussionmentioning
confidence: 99%
“…T 2 maps generated from 2D TSE by traditional exponential fitting, which is the most common acquisition pipeline in clinical studies, show poor T 2 accuracy. 32,33 New fitting methods, such as noisecorrected 33 and library-based fitting approaches, 34 along with new 3D acquisition schemes (quantitative double-echo steady-state 35,36 or isotropic 3D T 2 -prepared gradientecho 37 ), which enables higher in-plane spatial resolution and smaller slice thickness, may facilitate reproducible and precise T 2 estimates without the partial volume effect etc.…”
Section: Discussionmentioning
confidence: 99%
“…Because of an isotropic voxel size of 0.6 mm, the authors stated that the technique allows for multiplanar reformatting and T2 quantification in any plane of interest. 14 Eijgenraam et al showed that a sagittal 3D quantitative DESS (qDESS) MRI acquisition providing simultaneous T2 mapping and structural assessment of cartilage and meniscus, with full coverage of the knee and acquired within 5 minutes, can distinguish between different grades of radiographic knee OA. 15…”
Section: Quantitative Compositional Cartilage Mrimentioning
confidence: 99%
“…A T2-prepared fast-field echo knee scan of a healthy female volunteer (26y) was performed at 3T, using a 16-channel knee coil. The sequence was adapted from Colotti et al [24], modified with selective water excitation, and a segment-time increased from 700 to 800 ms. Fully sampled and CS-VDA (R = 3) data were scanned in an interleaved fashion, for T2-…”
Section: Prospective Undersampling Of In Vivo Human Knee Datamentioning
confidence: 99%